Development of a Free-Free Transverse Beam Model Using Lateral Vibrations of Beam Conventional Method during Seismic Activity - Salim, Mohd Azli; Noordin, Aminurrashid; Akop, Mohd Zaid (Canadian Center of Science and Education, 2011)
This paper expresses the derivation of Free-Free Transverse Beam Model using lateral vibration of beam conventional method during Seismic Activity. Derivation from three mathematical models gives coshβLcosβL = 1. Then by numerical software, the graph of those mathematical models is plotted. From the plots, and using equations, the natural frequencies of those three models are identiﬁed at values of 389.5 rad/s, 2440.9 rad/s, and 6825 rad/s for ω respectively.